2005
DOI: 10.1093/jn/135.8.1903
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein and Exercise Have Additive Effects on Body Composition during Weight Loss in Adult Women

Abstract: This study examined the interaction of 2 diets (high protein, reduced carbohydrates vs. low protein, high carbohydrates) with exercise on body composition and blood lipids in women (n = 48, approximately 46 y old, BMI = 33 kg/m(2)) during weight loss. The study was a 4-mo weight loss trial using a 2 x 2 block design (Diet x Exercise). Diets were equal in total energy (7.1 MJ/d) and lipids ( approximately 30% energy intake) but differed in protein content and the ratio of carbohydrate:protein at 1.6 g/(kg . d) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
242
6
21

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(287 citation statements)
references
References 36 publications
18
242
6
21
Order By: Relevance
“…For example, resistance exercise or high protein diets may modify the proportion of weight loss resulting from body fat versus lean tissue. [38][39][40] A more comprehensive model of macronutrient metabolism and body composition change would be required to model such factors. 41 …”
mentioning
confidence: 99%
“…For example, resistance exercise or high protein diets may modify the proportion of weight loss resulting from body fat versus lean tissue. [38][39][40] A more comprehensive model of macronutrient metabolism and body composition change would be required to model such factors. 41 …”
mentioning
confidence: 99%
“…There is evidence that high-protein diets induce a number of favourable changes along with weight loss (reduction in body fat, improvement in lipidaemic and glycaemic profiles and resting blood pressure) (2,4) . The addition of exercise (aerobic and/or resistance) to a high-protein diet had additive effects on body composition during weight loss (5) .Despite the popularity of high-protein diets, few studies have investigated their effects on exercise performance (6,7) . These studies reported that a 7 d high-protein diet decreased endurance (aerobic) performance of recreational and trained athletes.…”
mentioning
confidence: 99%
“…Muscle glycogen is the major energy source during high-intensity resistance exercise, and glycogen depletion is observed earlier in fast-twitch than slow-twitch fibres (8) . Thus, the lower carbohydrate content of a high-protein diet may result in reduced pre-exercise muscle glycogen levels and precipitate fatigue during resistance exercise.Although resistance exercise is recommended to individuals on high-protein diets for additional positive effects on body composition (5) , the effects of a high-protein diet on strength * Corresponding author: Dr Konstantina Dipla, fax þ11 30 2310 992186, …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of protein:carbohydrate manipulation on cholesterol was inconsistent. While most studies found that HP and HC diets had no differential effects on total and LDL cholesterol levels, some have shown that either HP or HC diets produced better outcomes [67,73,74,86,87]. HP diets were also found to result in higher fasting glucose levels compared with HC diets during weight loss [82][83][84]87].…”
Section: Moderate Carbohydrate High-protein Low-fat Diets (~40% Carmentioning
confidence: 99%